China Calls for Smarter Standards for Its World-Class Universities - Zha, Qiang (International Higher Education, 2016)
China recently launched a new stage of world-class university campaign, and emphasized developing the “Chinese characteristics” this time. Arguably, global rankings remain the most powerful illustration of who can claim world-class standing, which in turn renders the “Chinese characteristics” in question. This article argues that China would benefit from a kind of explicit “Chinese standards” to help establish a clearer direction for higher education development in the country.